The Analysis of Aquatic Chemical Parameters in Kurapan Lake and Sambas River, Sepantai Village, Sambas - Nurul Fatimah Yunita; Beryaldi Agam; Maryono Maryono; Dewi Merdekawati (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
This research aims to measure the chemical parameters of water quality. The parameters measured were pH, DO, BOD, COD, Nitrate, Ammonia, and Phosphate. The results of this research showed the pH scale range of 6.05 – 6.28, DO range of 5.16 – 7.00 mg/l, BOD range of 1.38 – 8.68 mg/l, COD range of 7.89 – 47.33 mg/l, Nitrate range of 0.31 – 0.38 mg/l, Ammonia of 0.04 – 0.07 mg/l, and Phosphate range of 1.24 – 1.27 mg/l. Hence, the chemical parameter of water quality values indicated that pH, Nitrate and, Ammonia met water quality standards for designated beneficial water uses